ANALISIS PERILAKU KEUANGAN PADA PELAKU UMKM DEPOK - Nabil Zamaksyary (2020)
This study aims to determine the effect of financial literacy, and financial attitude on financial behavior in micro, small and medium enterprises in the district of Beji, Depok City. the population in this study were all micro, small and medium enterprises in the district of Beji, amounting to 99 businesses. the sample size used was 80 respondents with a probability sampling method, especially simple random sampling. The data collection is used through questionnaires. The analysis technique used is the PLS (Partial Least Square) analysis method. the results of this study indicate that financial literacy, and financial attitude have a significant effect on financial behavior.